The Role of Service Quality and Environmental Factors on Restaurant Customer Satisfaction - Aryal, Narayan Prasad; Rokaya, Susma; Khadka, Kumar; Sah, Sarita Kumari (Nepalese Journal of Business and Management Studies, 2024)
Service quality and environmental factors are becoming more and more important in today’s restaurant sector as major drivers of profitability and long-term success. Thus, the goal of this study is to ascertain how service quality dimensions, measured by assurance and empathy and similarly, environmental factor dimensions, measured by spatial layout, and interior design are related to customer satisfaction, with a focus in the restaurants of Koteshwor area. The study adopts a thorough methodological framework and uses a quantitative research design and deductive reasoning methodology based in expectancy value theory. A mix of descriptive, relational, and causal research designs were used to gather information from 137 customers of Koteshwor area’s restaurants. The study employed a non-probability sampling approach, specifically convenience sampling, due to its easy access to participants. A self-administered questionnaire was developed to evaluate how assurance, empathy, spatial layout, and interior design affect customer satisfaction. Article History Received: 19 March 2024 Revised: 26 April 2024 Accepted: 22 July 2024 Vol. 3, No. 1, Page: 55-72 Corresponding Author* shahsarita768@gmail.com Several statistical tools, such as mean, median, frequency, standard deviation, independent sample t-tests, correlation, and regression analyses, were applied during the data analysis process. The study’s conclusions showed that assurance, empathy, spatial layout and interior design have positive and significant impact on customer satisfaction. Moreover, the findings indicate that there are no gender-specific differences in the perception of assurance, empathy, or interior design, but there is a gender-specific difference in the perception of spatial layout.